2021
DOI: 10.1021/acs.inorgchem.1c02948
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Functionalized Zirconium Metal–Organic Cages for Efficient CO2/N2 Separation

Abstract: Global warming associated with CO 2 emission has led to frequent extreme weather events in recent years. Carbon capture using porous solid adsorbents is promising for addressing the greenhouse effect. Herein, we report a series of robust metal− organic cages (MOCs) featuring various functional groups, such as methyl and amine groups, for CO 2 /N 2 separation. Significantly, the amine-group-functionalized MOC-QW-3-NH 2 displays the best selective CO 2 adsorption performance, as confirmed by singlecomponent adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The similar kinetic diameters and boiling points of C 2 H 2 , C 2 H 4 , and CO 2 make the design of robust physisorbents with simultaneously high uptake and selectivity extremely challenging. Porous materials such as porous silica, activated carbons, zeolites, porous aromatic frameworks (PAFs), metal–organic frameworks (MOFs), metal–organic cages, hydrogen-bonded organic frameworks (HOFs), and covalent organic frameworks (COFs) are potential candidates with excellent adsorption capacity and selectivity. For example, Zhang et al reported a highly stable and flexible HOF with suitable pore size for selective capture of ethylene, which can effectively separate C 2 H 2 /C 2 H 4 through a gate-opening effect at 313 K .…”
Section: Introductionmentioning
confidence: 99%
“…The similar kinetic diameters and boiling points of C 2 H 2 , C 2 H 4 , and CO 2 make the design of robust physisorbents with simultaneously high uptake and selectivity extremely challenging. Porous materials such as porous silica, activated carbons, zeolites, porous aromatic frameworks (PAFs), metal–organic frameworks (MOFs), metal–organic cages, hydrogen-bonded organic frameworks (HOFs), and covalent organic frameworks (COFs) are potential candidates with excellent adsorption capacity and selectivity. For example, Zhang et al reported a highly stable and flexible HOF with suitable pore size for selective capture of ethylene, which can effectively separate C 2 H 2 /C 2 H 4 through a gate-opening effect at 313 K .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Wei and co-workers reported a series of three isostructural MOCs constructed from the trinuclear Zr-cluster and terephthalate, 2-methylterephthalate, and 2-aminoterephthalate. 60 Among the series, the amine-functionalised MOC (built on 2-aminoterephthalate) exhibited the largest CO 2 uptake (26.8 mL g −1 , 298 K, 1 bar) and the highest CO 2 /N 2 selectivity (23, based on the ideal adsorption solution theory, IAST). To evaluate the practical dynamic selectivity performance, dynamic transient breakthrough experiments were performed under ambient conditions, in which CO 2 /N 2 (15 : 85, v/v) mixtures flowed through a packed column.…”
Section: Harmful Gasesmentioning
confidence: 99%
“…Similarly, such a strategy can be extended to MOCs by modifying organic linkers with desirable functional groups for different gas sorption and separation. For example, Qin et al and Lee et al found that the amino- and sulfonyl-based cages exhibited good CO 2 adsorption while the flexible azobenzene ligands aid CO 2 adsorption through cage expansion upon visible light irradiation …”
Section: Applicationsmentioning
confidence: 99%
“…68 Similarly, such a strategy can be extended to MOCs by modifying organic linkers with desirable functional groups for different gas sorption and separation. For example, Qin et al and Lee et al found that the amino- 69 and sulfonyl-based 17 cages exhibited good CO 2 adsorption while the flexible azobenzene ligands aid CO 2 adsorption through cage expansion upon visible light irradiation. 36 In our recent work, we replaced the NH 2 on ZrT-1-NH 2 with a tetrazole group to increase the cage affinity toward C 2 H 2 in order to tackle the challenge of separating valuable C 2 H 2 from C 2 H 4 and CO 2 .…”
Section: Gas Sorption and Separationmentioning
confidence: 99%